2018
DOI: 10.6007/ijarbss/v8-i4/4000
|View full text |Cite
|
Sign up to set email alerts
|

A Linkage between Entrepreneurial Leadership and SMEs Performance: An Integrated Review

Abstract: Previous researches have shown that characteristics of entrepreneurial leadership have influence organisational performance regardless of the organisational size. This paper was set to review the relationship of vision, innovation, proactiveness and risk-taking on Small Medium Enterprises (SMEs) performance. This resulted to the question that does entrepreneurial leadership (i.e vision, innovation, proactiveness and risk-taking) significantly relate to performance of SMEs? From the review of related literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 34 publications
2
20
0
4
Order By: Relevance
“…It is worthy of note that the literature review underscores the importance and role of training in the activity of entrepreneurship project. Consequently, the outcome of this study has re-echoed the thoughts and findings of prior scholarly works of Zainol, Daud, Shamsu, Abubakar andHalim 2018 andChowdhury, Alam andArif (2013); Arisi-Nwugballa, Elom and Onyeizugbe (2016). Additionally, the findings reiterate the affirmative role of innovativeness in the cause of developing SME in Abuja Nigeria.…”
Section: Discussion On Findingssupporting
confidence: 60%
See 1 more Smart Citation
“…It is worthy of note that the literature review underscores the importance and role of training in the activity of entrepreneurship project. Consequently, the outcome of this study has re-echoed the thoughts and findings of prior scholarly works of Zainol, Daud, Shamsu, Abubakar andHalim 2018 andChowdhury, Alam andArif (2013); Arisi-Nwugballa, Elom and Onyeizugbe (2016). Additionally, the findings reiterate the affirmative role of innovativeness in the cause of developing SME in Abuja Nigeria.…”
Section: Discussion On Findingssupporting
confidence: 60%
“…Entrepreneurial training aids the SMEs operator, manager or owner to device means of survival in today's business environment. It also introduces the SMEs operator/manager to the challenges that the business environment poses and the evolving methods of surmounting those challenges (Zainol, Daud, Shamsu, Abubakar & Halim 2018).…”
Section: Entrepreneurial Training and Smes Developmentmentioning
confidence: 99%
“…52 Studies by Renko, El Tarabishy, et al 25 and Gupta et al 41 offered a comprehensive EL construct, arguing that this leadership influences and directs the synergetic performance of group members toward accomplishing those organizational goals that relate to recognizing and exploiting contingencies, which ultimately influence the success of EL. Drawing from the notion of "cast enactment" in EL theory proposed by Gupta et al 41 large numbers of the studies [53][54][55][56][57] have suggested EL as the most influential factor for innovative behavior, and highlighted its importance in stimulating and fostering innovation in highly dynamic and competitive business environments. So, it is critical to understand the mechanisms through which EL influences employees' innovative work behavior, and stimulates innovation performance of the organization.…”
Section: Introductionmentioning
confidence: 99%
“…The involvement of the manager in all business processes, his accumulated experience (Carson, 1990), and his personal characteristics (Marques and Ferreira, 2009;Ng and Kee, 2018;Zainol et al, 2018) may all have an impact on the promotion of innovation in small businesses.…”
Section: Characteristics Of Small Businessesmentioning
confidence: 99%
“…This study addresses the contribution of open innovation (OI) tools to the promotion of innovation in small businesses in the industry and craft sectors. In a rapidly changing global world, innovation is vital to all businesses (Marques and Ferreira, 2009;Porter, 1996;Teece et al, 1997;Zainol et al, 2018), but the innovation process carries risks and its management is complex (Chesbrough, 2003), making it particularly difficult to promote innovation in small businesses, especially in view of their resource constraints and size disadvantages. In addition, small businesses must cope with various hardships that hinder their innovation, such as difficulty in obtaining suitable talent, lack of appropriate infrastructure, and scant funding (Harel and Kaufmann, 2016;Kleinknecht, 1989;Lee et al, 2010;Van de Vrande et al, 2009).…”
Section: Introductionmentioning
confidence: 99%